2021
DOI: 10.3390/cells10071661
|View full text |Cite
|
Sign up to set email alerts
|

Lymphatic Trafficking in the Eye: Modulation of Lymphatic Trafficking to Promote Corneal Transplant Survival

Abstract: (Lymph)angiogenesis into the cornea prior to and after corneal transplantation is a critical risk factor for allograft rejection. Lymphatic vessels even more than blood vessels seem important in mediating immune responses, as they facilitate allograft sensitization in the draining lymph nodes. Thus, the concept of modulating lymphatic trafficking to promote corneal graft survival seems promising. A variety of approaches has been developed to inhibit progressive lymphangiogenesis in experimental settings. Recen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 138 publications
(233 reference statements)
0
21
0
Order By: Relevance
“…For instance, inhibiting the lymphatic vasculature led to increased inflammation in mouse models of skin inflammation [100,101], inflammatory bowel disease [102,103] and rheumatoid arthritis [104]. However, inhibiting this process improves graft survival in corneal transplantation [105,106].…”
Section: Neutrophil Contributions To Lymphangiogenesismentioning
confidence: 99%
“…For instance, inhibiting the lymphatic vasculature led to increased inflammation in mouse models of skin inflammation [100,101], inflammatory bowel disease [102,103] and rheumatoid arthritis [104]. However, inhibiting this process improves graft survival in corneal transplantation [105,106].…”
Section: Neutrophil Contributions To Lymphangiogenesismentioning
confidence: 99%
“…We have arrived at this nuanced understanding of apoptosis in BV regression as a result of much research, and to our knowledge, there have been few investigations of the role of apoptosis in LV regression. In a study, Hou et al (2021) utilized ultraviolet A light crosslinking to induce regression of corneal LVs and BVs in an apoptosis-dependent manner. Perhaps in an example of migration-dependent temporary LV regression, Gur-Cohen et al (2019) demonstrated a transient dissociation of LVs from the hair follicle stem cell niche after the onset of the hair cycle and noted the absence of apoptosis in this context.…”
Section: Learning From Blood Vessel Regressionmentioning
confidence: 99%
“…Despite the advent of human leukocyte antigen matching and the administration of immunosuppressants, allograft rejection remains the leading cause of graft failure beyond 1 year post-transplantation ( Yamakawa et al, 2018 ; Wong, 2020 ). Lymphangiogenesis has been observed following transplantation of solid organs such as the heart, kidney, and lungs as well as the normally avascular cornea ( Wong, 2020 ; Hou et al, 2021 ). This proliferation of novel LVs connects the transplanted organ to the systemic lymphatic circulation, thereby facilitating the arrival of antigen-presenting cells (APCs) to draining lymph nodes ( Donnan et al, 2021 ).…”
Section: Reflecting On Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to regulating interstitial fluid homeostasis, the lymphatics are an integral component of the immune system, facilitating the transport of immune cells, pathogens, and antigens [101] from the sites of injured and infected tissues to draining lymph nodes (dLNs) for generation of protective T and B cell responses [101,102]. Allied to this, they also provide a key route for exit of immune cells during the resolution of tissue inflammation, not only following myocardial infarction, but also lung injury and allograft rejection [97,[103][104][105]. In normal resting tissue the numbers of immune cells migrating in afferent lymphatics are small, comprising mainly T-cells (approximately 90%) and immature antigen presenting dendritic cells (DCs) engaged in background immune surveillance.…”
Section: Exit Of Immune Cells From the Infarcted Heart-the Role Of Cardiac Lymphaticsmentioning
confidence: 99%